Does the number of mucosal immune cells differ in irritable bowel syndrome and its subtypes? - Raim İliaz and Filiz Akyüz and Gülçin Yeğen and Aslı Örmeci and Suut Göktürk and Ümit Akyüz and Bülent Baran and Özlem Mutluay and Sami Evirgen and Çetin Karaca and et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Recently, mucosal inflammation has been proposed to be one of the mechanisms underlying the pathophysiology of irritable bowel syndrome (IBS); however, there are controversial results regarding this hypotheses. Our aim was to evaluate immune cell infiltration in rectal and ileal biopsy specimens of patients with IBS and to compare it with those of healthy controls. Materials and Methods: In total, 36 patients with IBS (15 with diarrhea and 21 with constipation) and 16 healthy volunteers were enrolled. Ileocolonoscopy and ileal/rectal biopsies were performed. Rectal and terminal ileal biopsy specimens were evaluated for mucosal immune cell infiltration using immunohistochemical analysis. Serotonin positivity as well as counts of intraepithelial lymphocytes (IEL) and CD4+, CD8+, CD20+, and CD3+ cells were determined by a single pathologist who is an expert in the gastrointestinal system. Results: CD3+ and CD4+ cell counts in rectal and terminal ileal biopsy specimens were lower in the IBS group than in the controls. Conversely, there was no statistically significant difference between the IBS and control groups in terms of serotonin positivity as well as counts of IEL and CD20+ and CD8+ cells. Comparison between the IBS subgroups revealed a higher number of IEL in rectal biopsy specimens of the diarrhea dominant group. In the IBS subgroups, immune cell counts in terminal ileal and rectal biopsy specimens showed a positive correlation. Conclusion: IBS and its subgroups showed lower immune cell counts than the controls in our study. These results indicate that there is no significant mucosal inflammation in homogeneous groups of patients with IBS. Rectal biopsies may be sufficient for the evaluation of inflammation in IBS. Cite this article as: İliaz R, Akyüz F, Yeğen G, et al. Does the number of mucosal immune cells differ in irritable bowel syndrome and its subtypes? Turk J Gastroenterol 2018; 29: 384-91.